(untitled) (Research, Society and Development, 2020)
Objective: To present the somatoform disorders most commonly observed in the daily medical clinic, relating them to the current pandemic situation of COVID-19. Methods: was conduced a descriptive and exploratory bibliographic review, with a qualitative approach, using the PubMed, LILACS, SciELO, and ScienceDirect databases; with the following descriptors: Somatização, Transtornos Somatoformes, Psicossomática, Hipocondria, Transtorno neurovegetativo, Dor crônica, Pandemia, Epidemia, COVID-19, Coronavírus e o boleano AND. 18 references were included. Results: The pandemic situation and the most effective measures to contain the disease, which are isolation and social detachment, generate new stressors for individuals and stimulate the onset or worsening of somatoform disorders. The ICD-10 divide such disorders into seven subtypes, which have somatic signs and symptoms in common without medical explanation and cause impairment in the individual’s daily functioning. The incidence and prevalence of somatoform disorders are expected to increase with the pandemic, and to persist even after the crisis has resolved. Conclusions: It is of great importance that, given the pandemic situation of COVID-19, patients with somatoform disorders receive comprehensive and appropriate care, which takes into account the biopsychosocial and spiritual factors specific to each individual. Therefore, it is essential that health professionals know how to recognize both the specific characteristics of the disease and its association with the current scenario so can be made that the proper diagnosis and treatment can be made.